Approaches in media, role and mobilization - Siemesm, Hamida (ALBAHITH ALALAMI, 2005)
There is a natural problem raised by the issue of media performance. As a separate activity and express its own capabilities. This problem can be framed in the form of a question: Is media performance merely a reflection of the activity of other sectors of society, especially political and economic, and what links them to other societal sectors of interrelated relations? Is the media limited to mere transfer, or is it an industry with its own mechanisms and rules? The answer may seem somewhat complicated if we handle media with research and study in general, but the issue may be less complicated when it comes to Arab media, because its data may add another setback to the overall Arab setbacks.